Алгоритм оптимізації розподілу радіочастотних ресурсів у SDR-базованих LTE мережах з адаптивною просторово-часовою обробкою сигналів - Жуга, Ю. С. (ХНУРЕ, 2025)
This work presents a comprehensive approach to optimizing resource allocation in mobile communication systems through adaptive spatial temporal signal processing techniques. An SDR-based platform was implemented using LimeSDR and the srsRAN software suite, integrating harmonic analysis and predictive load modeling. Experimental results demonstrate significant improvements in spectral efficiency, a 30% reduction in computational load, and a 20% enhancement in energy efficiency. The proposed methodology provides high adaptability to variable traffic conditions, making it a promising solution for next generation LTE and beyond mobile networks.
Keywords: розподіл радіочастотних ресурсів; просторово-часова обробка сигналів